Design of a Novel Multi-Epitope Vaccine Against Echinococcus granulosus in Immunoinformatics - Yu, Mingkai; Zhu, Yuejie; Li, Yujiao; Chen, Zhiqiang; Sha, Tong; Li, Zhiwei; Zhang, Fengbo; Ding, Jianbing (Frontiers in Immunology, 2021)
All the time, echinococcosis is a global zoonotic disease which seriously endangers public health all over the world. In order to speed up the development process of anti-Echinococcus granulosus vaccine, at the same time, it can also save economic cost. In this study, immunoinformatics tools and molecular docking methods were used to predict and screen the antigen epitopes of Echinococcus granulosus, so as to design a polypeptide vaccine containing B- and T-cell epitopes. The multi-epitope vaccine could activate B lymphocytes to produce specific antibodies theoretically, which could protect the human body against Echinococcus granulosus infection. It also could activate T lymphocytes and clear the infected parasites in body. In this study, four CD8+ T-cell epitopes, three CD4+ T-cell epitopes and four B-cell epitopes of Protein EgTeg were identified by immunoinformatics methods. Meanwhile, three CD8+ T-cell epitopes, two CD4+ T-cell epitopes and four B-cell epitopes of Protein EgFABP1 were identified. Finally, we constructed the multi-epitope vaccine using linker proteins. Based on the traditional methods of antigen epitope prediction, combined with molecular docking technology, we further verified and optimized the prediction results, and improved the precision and accuracy of the results.